f(x) *g(x) = (x-3)(x+11) = x^2 +11x -3x -33 = x^2 +8x -33
Sorry if its wrong :(
Step-by-step explanation:
<u>Given</u><u>:</u>
Central Enlargement.
AC=4
AB=5
BC=3
Opp=3
Hyp=5
<u>Required</u><u>:</u>
Sin<A
<u>Formula</u><u>:</u>
Sin<A=Opp/hyp
<u>Solution</u><u>:</u>
Sin<A=Opp/Hyp
Sin<A=3/5 or 0.6
Answer:
22.5 cm
Step-by-step explanation:
9 inches=9×2.5 cm =22.5 cm
Answer:
$27.87
Step-by-step explanation:
if it is 1 by 2 you would multiply 1 x 2 and get 2 then multiply 13.87 x 2 to get 27.87 and it leaves you with $27.87